Synthesis and Characterization of Ethanolic Extract of Red Betel Leaf as an Antiseptic Gel - Harimurti, Sabtanti; Hidayaturahmah, Rizky; Arsito, Puguh Novi; Febriansah, Rifki; Widada, Hari (Sanata Dharma University, 2024)
Hand hygiene is one way to maintain health. There are several ways to clean hands, namely by washing hands and applying a hand sanitizer. The use of hand sanitizer is increasing due to its practical nature. Utilizing natural materials for preparing hand sanitizer widely available around us will be beneficial, one of which is red betel leaf which some people of Indonesia empirically use for antiseptic. This study aims to develop antiseptic gel preparations with ethanolic extracts from red betel leaves. The extraction was done using maceration with 70% ethanol solvent. The formula for choosing a carbomer as a gelling agent with the red betel leaf extract concentration was 0%, 2.5%, 5%, 10%, and 15%. The assessments of the gel were physical and antiseptic evaluations. The physical evaluations included an organoleptic, pH, viscosity, adhesion, and dispersion tests. The antiseptic activity was determined by a replica method. The physical evaluation results of red betel gel revealed that the higher the red betel leaf extract levels are, the darker the green color will be, and the lower the pH and viscosity will be. Furthermore, the antiseptic activity showed that red betel extract gel effectively reduced the number of bacterial colonies.